MATLAB GUI Based Sensor Array Processing Estimation Methods and Performance Analysis Simulator - Kucuk, Kerem; Kelebekler, Ersoy; Kavak, Adnan (2007 IEEE 15th Signal Processing and Communications Applications, 2007)
This paper presents a simulator designed to enable simulations and performance analysis of different estimation algorithms and methods in the sensor array processing problems for postgraduate level statistical and array signal processing lesson. This simulator has been prepared using graphical user interface (GUI) capabilities of MATLAB being used widespread in engineering subjects. User constitutes simulation environment itself by entering the desired parameters and is able to choose different methods and algorithms for frequency, direction of arrival and signal waveform estimations. Antenna configuration has been chosen as uniform linear array (ULA). The aim is to develop a simulator which provides the postgraduate students to fully comprehend the methods used to truly find related parameters in simulation conditions and enables to make a performance analysis of the methods by means of root-mean squared error (RMSE) in the same conditions.